2022
DOI: 10.1002/adfm.202202415
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Growth across the Twin Boundaries of Copper Substrate

Abstract: Twin crystals, the formation energy of which is much smaller than that of ordinary grain boundaries, widely exist in the annealed copper and are hard to eliminate. The study of the effects of twin boundaries on graphene growth is of great significance to the understanding of graphene epitaxy. However, there are few studies on the effects of twin boundaries on the graphene growth process. Here, this article experimentally demonstrates that graphene islands are subjected to different compressive strains from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…High-index surfaces closely resemble vicinal Cu(111) surfaces when n < 3, whereas they should be classified as vicinal Cu(110) and Cu(100) surfaces when n > 3. In addition, when the reported experimental work is searched, the growth of graphene islands on several high-index Cu surfaces is summaried in panels b–j of Figure and Figure S3 of the Supporting Information. We can see that the experimentally observed alignment of the graphene islands is in perfect agreement with our theoretical prediction, which strongly validates our theory.…”
Section: Methodsmentioning
confidence: 99%
“…High-index surfaces closely resemble vicinal Cu(111) surfaces when n < 3, whereas they should be classified as vicinal Cu(110) and Cu(100) surfaces when n > 3. In addition, when the reported experimental work is searched, the growth of graphene islands on several high-index Cu surfaces is summaried in panels b–j of Figure and Figure S3 of the Supporting Information. We can see that the experimentally observed alignment of the graphene islands is in perfect agreement with our theoretical prediction, which strongly validates our theory.…”
Section: Methodsmentioning
confidence: 99%
“…(4) In addition to single‐crystal Cu foils, single‐crystal graphene could also be synthesized on Cu foils with twin crystals. Through analysis of the geometrical relationships of the twin crystal planes, it is found that the single‐crystal graphene could be epitaxially grown on specific twinned substrates 25,26 . In short, the growth of large‐scale high‐quality graphene films on Cu foils has been achieved.…”
Section: Figurementioning
confidence: 99%
“…Through analysis of the geometrical relationships of the twin crystal planes, it is found that the single-crystal graphene could be epitaxially grown on specific twinned substrates. 25,26 In short, the growth of large-scale high-quality graphene films on Cu foils has been achieved. The prospect of producing large-scale, highquality, single-crystal graphene on Cu foils via a roll-toroll process appears to be feasible, indicating a new era of scalable and efficient graphene production.…”
mentioning
confidence: 99%
“…These models emit uniform and bright luminescence under X‐ray excitation (Figure 3a). Flexible scintillator devices have a good resistance to mechanical deformation and can be tightly attached to the curved surfaces of objects for X‐ray imaging, thereby achieving better contrast and higher resolution [19] . Considering the compatibility of 1‐rod with various polymers, it was combined with PDMS to prepare a flexible scintillator screen.…”
Section: Figurementioning
confidence: 99%